Advertisements
Advertisements
Question
Solution
\[\int\frac{\left( x^3 + 8 \right)\left( x - 1 \right)}{\left( x^2 - 2x + 4 \right)}dx\]
\[ = \int\frac{\left( x^3 + 2^3 \right) \left( x - 1 \right)}{\left( x^2 - 2x + 4 \right)}dx \]
\[ = \int\frac{\left( x + 2 \right) \left( x^2 - 2x + 4 \right) \left( x - 1 \right)}{\left( x^2 - 2x + 4 \right)} dx \left[ \therefore a^3 + b^3 = \left( a + b \right) \left( a^2 - ab + b^2 \right) \right]\]
\[ = \int \left( x + 2 \right) \left( x - 1 \right)dx\]
\[ = \int\left( x^2 - x + 2x - 2 \right)dx\]
\[ = \int\left( x^2 + x - 2 \right)dx\]
\[ = \int x^2 dx + \text{∫ x dx} - 2 \int1dx\]
\[ = \frac{x^3}{3} + \frac{x^2}{2} - 2x + C\]
APPEARS IN
RELATED QUESTIONS
` ∫ {x-3} /{ x^2 + 2x - 4 } dx `
\[\int\left( e^\text{log x} + \sin x \right) \text{ cos x dx }\]
\[\int\frac{x^3}{\sqrt{1 + x^2}}dx = a \left( 1 + x^2 \right)^\frac{3}{2} + b\sqrt{1 + x^2} + C\], then
\[\int\sqrt{\frac{1 - x}{x}} \text{ dx}\]
\[\int\frac{5 x^4 + 12 x^3 + 7 x^2}{x^2 + x} dx\]